2023
DOI: 10.21203/rs.3.rs-2543463/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deep Learning Dynamic Allostery of G-Protein-Coupled Receptors

Abstract: G-protein-coupled receptors (GPCRs) are the largest superfamily of human membrane proteins and represent primary targets of ~ 1/3 of currently marketed drugs. Allosteric modulators have emerged as more selective drug candidates compared with orthosteric agonists and antagonists. However, many X-ray and cryo-EM structures of GPCRs resolved so far exhibit negligible differences upon binding of positive and negative allosteric modulators (PAMs and NAMs). Mechanism of dynamic allosteric modulation in GPCRs remains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…The high-resolution structures revealed that compound 9n binds to a previously unidentified crevice between TM5-TM6-ECL2 on the extracellular side (Fig. 4c) 37,38 .Detailed analysis showed that compound 9n predominantly forms hydrophobic interactions with neighboring residues in this pocket (Fig. 4c).…”
Section: Unique Allosteric Agonist Binding Pocketmentioning
confidence: 96%
See 1 more Smart Citation
“…The high-resolution structures revealed that compound 9n binds to a previously unidentified crevice between TM5-TM6-ECL2 on the extracellular side (Fig. 4c) 37,38 .Detailed analysis showed that compound 9n predominantly forms hydrophobic interactions with neighboring residues in this pocket (Fig. 4c).…”
Section: Unique Allosteric Agonist Binding Pocketmentioning
confidence: 96%
“…Compared to orthosteric ligands, allosteric modulators bind to nonconserved sites and offer promising opportunities for the development of novel therapeutic approaches with improved receptor selectivity and reduced side-effects [34][35][36] . However, despite their potential, only a limited number of class A GPCR structures in complex with positive allosteric modulators (PAMs) have been reported 37,38 ; this highlights the necessity for further investigation into the binding and actions of PAMs. The existing structures reveal that PAMs bind to four broad regions within class A GPCRs (Fig.…”
Section: Unique Allosteric Agonist Binding Pocketmentioning
confidence: 99%